Amulet 2 : The stonekeeper's curse. The stonekeeper's curse - Kibuishi, Kazu, 1978- (New York : Graphix, 2009)
Emily and her brother, Navin, head for Kanalis in order to find the antidote for the poison that has sickened their mother.
Booklist
Horn Book
School Library Journal
Booklist, October 2009
Horn Book, April 2010
Kirkus Review, September 2009
Keywords: Magic -- Comic books, strips, etc -- Juvenile fiction; Single parent families -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Fantasy; Magic -- Fiction; Single parent families -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Graphic novels; Magic -- Comic books, strips, etc -- Fiction; Single parent families -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels